Engineered Fibrillar Fibronectin Networks as Three‐Dimensional Tissue Scaffolds. Issue 46 (30th September 2019) - Jordahl, Stacy; Solorio, Luis; Neale, Dylan B.; McDermott, Sean; Jordahl, Jacob H.; Fox, Alexandra; Dunlay, Christopher; Xiao, Annie; Brown, Martha; Wicha, Max; Luker, Gary D.; Lahann, Joerg
Abstract: Extracellular matrix (ECM) proteins, and most prominently, fibronectin (Fn), are routinely used in the form of adsorbed pre‐coatings in an attempt to create a cell‐supporting environment in both two‐ and three‐dimensional cell culture systems. However, these protein coatings are typically deposited in a form which is structurally and functionally distinct from the ECM‐constituting fibrillar protein networks naturally deposited by cells. Here, the cell‐free and scalable synthesis of freely suspended and mechanically robust three‐dimensional (3D) networks of fibrillar fibronectin (fFn) supported by tessellated polymer scaffolds is reported. Hydrodynamically induced Fn fibrillogenesis at the three‐phase contact line between air, an Fn solution, and a tessellated scaffold microstructure yields extended protein networks. Importantly, engineered fFn networks promote cell invasion and proliferation, enable in vitro expansion of primary cancer cells, and induce an epithelial‐to‐mesenchymal transition in cancer cells. Engineered fFn networks support the formation of multicellular cancer structures cells from plural effusions of cancer patients. With further work, engineered fFn networks can have a transformative impact on fundamental cell studies, precision medicine, pharmaceutical testing, and pre‐clinical diagnostics. Abstract : Fibrillar fibronectin (fFn) networks are freely suspended across porous polymer structures without the use of cells. Engineered fFn networks enable in vivo implantation or in vitro expansion of various cell types including patient breast cancer cells that otherwise fail to survive on tissue culture polystyrene.